Reguły dyskursu obywatelskiego a mechanizmy dyskursu publicznego (na przykładzie stowarzyszeń i ruchów działających na rzecz edukacji) - Ciesek, Bernadetta (Papers in Linguistics, 2019)
The article discusses the rules of civil discourse based on some practices of civil associations for education. The analysis focuses on social, cultural and political contexts in which the discourse has been developing. The influence of the mechanisms of public discourse on the participation of symbolic elites has also been discussed.